2015
DOI: 10.1007/978-3-319-24021-3_7
|View full text |Cite
|
Sign up to set email alerts
|

Solving Polynomial Systems in the Cloud with Polynomial Homotopy Continuation

Abstract: Polynomial systems occur in many fields of science and engineering. Polynomial homotopy continuation methods apply symbolic-numeric algorithms to solve polynomial systems. We describe the design and implementation of our web interface and reflect on the application of polynomial homotopy continuation methods to solve polynomial systems in the cloud. Via the graph isomorphism problem we organize and classify the polynomial systems we solved. The classification with the canonical form of a graph identifies newly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…Installing Macaulay2 on a Windows machine is an especially arduous task, creating an enormous barrier to entry for potential Windows users of the package. These are common challenges for specialized mathematical software, and like others before us we concluded that a cloud version of our software was a worthwhile venture (Bliss et al, 2015;Kastner et al, 2015). Amazon Web Services (AWS, available at https://aws.amazon.com/) is a subsidiary of Amazon, Inc. that sells cloud computing solutions.…”
Section: Macaulay2 In the Cloudsupporting
confidence: 74%
“…Installing Macaulay2 on a Windows machine is an especially arduous task, creating an enormous barrier to entry for potential Windows users of the package. These are common challenges for specialized mathematical software, and like others before us we concluded that a cloud version of our software was a worthwhile venture (Bliss et al, 2015;Kastner et al, 2015). Amazon Web Services (AWS, available at https://aws.amazon.com/) is a subsidiary of Amazon, Inc. that sells cloud computing solutions.…”
Section: Macaulay2 In the Cloudsupporting
confidence: 74%
“…Installing Macaulay2 on a Windows machine is an especially arduous task, creating an enormous barrier to entry for potential Windows users of the package. These are common challenges for specialized mathematical software, and like others before us we concluded that a cloud version of our software was a worthwhile venture (Bliss, Sommars, Verschelde, and Yu 2015;Kastner, Hinkelmann, and Stillman 2015).…”
Section: Macaulay2 In the Cloudsupporting
confidence: 72%
“…The focus of this paper is on the application of new technology to solve polynomial systems, in particular, cloud computing [BSVY15] and multicore shared memory parallelism accelerated with graphics processing units [VY15]. Our web interface offers phcpy in a SageMath [Sage], [SJ05] kernel or in a Python kernel of a Jupyter notebook [Klu16].…”
Section: Introductionmentioning
confidence: 99%